The correlation between tinnitus-specific and quality of life questionnaires to assess the impact on the quality of life in tinnitus patients - Van Hoof, Lauren; Kleinjung, Tobias; Cardon, Emilie; Van Rompaey, Vincent; Peter, Nicole (Frontiers in Neurology, 2022)
Introduction: Subjective tinnitus is often associated with a reduction in health-related quality of life (HRQoL). The HRQoL represents the impact of tinnitus on an individual’s life by addressing the physical, social, and psychological domains of health. A limited amount of studies has investigated the association between tinnitus and HRQoL questionnaires. The aim of this study was to examine the correlation between tinnitus-specific and HRQoL questionnaires in order to shorten fulfilling questionnaires, as it is often time-consuming. Material and Method: Eighty-five patients with tinnitus as primary complaint completed five questionnaires, including one general, two tinnitus-specific, and two generic HRQoL questionnaires: Tinnitus Sample Case History Questionnaire (TSCHQ), Tinnitus Functional Index (TFI), Tinnitus Handicap Inventory (THI), short version of World Health Organization Quality-of-Life (WHOQOL-BREF), and the eight-item short-form (SF-8).. Four simple linear regression models were used to analyze the relationship between the THI and TFI and the WHOQOL-BREF and SF-8. Results: A negative and strong correlation was found between the tinnitus questionnaires and the SF-8. More than half of the variability in the SF-8 scores could be explained by the TFI and THI, respectively 50.6% and 54.4% (all p<0.001). A strong negative regression was also found between the WHOQOL-BREF and the THI and TFI with a decrease in the determination coefficient of approximately 10% compared with the SF-8. The weakest correlation (regression coefficient of 0.628, p<0.001) was observed between the WHOQOL-BREF and the TFI, indicating that the WHOQOL-BREF mean score explained 39.4% of the TFI. When looking at the subdomain scores, a strong correlation was observed between the QoL subdomain of the TFI and a combination of the physical and psychological subdomain of the WHOQOL-BREF (r=-0.627, p<0.001). Conclusion: The QoL subdomain of the TFI gives good information about the physical and psychological health. Thus, the TFI is suitable to assess both tinnitus severity and the HRQoL. The coefficient of determination of the WHOQOL-BREF was slightly decreased compared to the SF-8, suggesting that the WHOQOL-BREF provides more specific information about HRQoL. If more specific information on HRQoL, such as ‘environment’ and ‘social relationships’, is required, it is recommended to use the WHOQOL-BREF.